Strictureplasty in Complex Crohn's Disease: Beyond the Basics - Strong, Scott A. (Clinics in Colon and Rectal Surgery, 2019)
The strictureplasty operation was originally adopted for use in selected patients with Crohn's disease to allow for bowel conservation. The procedure and its usage have evolved over time as experience and confidence with the technique has grown. The short- and long-term outcomes of strictureplasty compared with resection attest to its safety and durable efficacy.
Keywords: bowel conservation; Crohn's disease; short bowel; small bowel; strictureplasty